STUDI DESKRIPTIF MINAT CALON GURU SEKOLAH DASAR TERHADAP PENGGUNAAN ALAT PERAGA MATEMATIKA SETELAH PERKULIAHAN MEDIA DAN MODEL PEMBELAJARAN MATEMATIKA SD - Isna Rafianti; Etika Khaerunnisa (Jurnal Dinamika Pendidikan, 2015)
This research is motivated by the lack of interest of teachers in the use of props in the process of learning mathematics in elementary school. In accordance with the demands of the curriculum in 2013 and supported by the developed learning theory, learning mathematics is abstract object of study, students need an intermediary that props math-ematics, so that students can more easily understand the concepts that will be pre-sented, and in the end it can deliver students to solve mathematical problems, not only that proposed by the teacher but also the problems in life. The purpose of this study was to determine the interest of prospective elementary teachers on the use of props mathematics after getting lectures media and elementary mathematics learning model. By knowing the interest of prospective elementary teachers will be developed further realization of the state of the subject being studied. The method used is descriptive research, then the instruments used were questionnaires and interviews. The results of this study stated that the interest of prospective elementary teachers on the use of props after attending lectures media and elementary mathematics learning model is high over-all with a percentage of 76.70%.Keywords : Interest, Props Mathematics